NORMAL FUNCTION OF A VEHICLE AS A MEANS OF TRANSPORT OR A MACHINE FOR CARRYING OUT WORK IN MOTOR THIRD PARTY LIABILITY INSURANCE WITH SPECIAL REGARD TO THE LATEST RULINGS OF THE COURT OF JUSTICE OF THE EUROPEAN UNION (EU and comparative law issues and challenges series (ECLIC), 2018)
The European law of motor third party liability (MTPL) insurance is based on six directives. The failure of the directives in defining the concept of “use of vehicles” and the transposition of relevant rulings into of the Member States national laws have resulted in different national case-laws. The “use of vehicles” is the main prerequisite for the incurrence of the insurer’s liability concerning the damages awarded to persons harmed and legal positions have been adopted according to which the concept in question refers only to the use of a vehicle that is consistent with its normal function, i.e. as a means of transport in road traffic. This paper discusses the rulings of the Court of Justice of the European Union (CJEU), the highest judicial authority in the EU, regarding their interpretation of the concept of the “use of vehicles” in the Case C-162/13 and generation of legal instability in the EU motor insurance law. In this paper the author analyses the latest rulings of the CJEU in the Case C-514/16 in relation to the contested question whether the concept of “use of vehicles” also covers the use of vehicle as a machine generating motive power when the vehicle itself is not travelling. Considering the justification, and pointing out to the grounds of the judgement of the CJEU in the Case C-514/16, the author considers it necessary to examine the legal aspects of insurance protection and legal consequences of the aforementioned interpretation according to which the compulsory MTPL insurance refers also to damages resulting from the use of a vehicle when the vehicle is out of traffic.